The exploration of social and cultural challenges of Chinese-Filipino in Philippine society in the Mano Po film series - Aranda, Ma. Rita R. (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Mano Po film series (2002-2016) presents an intriguing and developing representation of Chinese-Filipino culture in the Philippines. Through its captivating plot and characters, this second longest-running film series in the Philippines sheds light on the challenges Chinese Filipinos continue to confront as they seek their social and cultural identity in Filipino culture. The present study seeks to investigate the extent to which the seven Mano Po films attempt, via filmic representation, to preserve and enrich the Chinese culture and traditions within the Filipino community. It investigates the activities, rituals, ceremonies, culture, and traditions depicted in the film using cultural studies as a tool for inquiry. The study's findings are that while Chinese Filipinos make concerted efforts to embrace and assimilate into Filipino culture, they do so while maintaining their rich cultural heritage and traditions. They may experience cultural dislocation within Philippine society. Yet, they strive to overcome these challenges by openly acknowledging their hybrid identity and liminal status to establish a peaceful relationship with both cultures. The study aims to cultivate a more profound understanding of Chinese Filipinos' endeavours to embrace Filipino culture while conserving their rich traditions. This understanding can foster greater cultural acceptance and harmony between the two communities as they seek social and cultural identity.